Software development to support decision making in the selection of nursing diagnoses and interventions for children and adolescents. - de Lima Silva, Kenya; Dora Martinez Évora, Yolanda; Santana Justo Cintra, Camila (Revista Latino-Americana de Enfermagem (RLAE))
Objective: to report the development of a software to support decision-making for the selection of nursing diagnoses and interventions for children and adolescents, based on the nomenclature of nursing diagnoses, outcomes and interventions of a university hospital in Paraiba. Method: a methodological applied study based on software engineering, as proposed by Pressman, developed in three cycles, namely: flow chart construction, development of the navigation interface, and construction of functional expressions and programming development. Result: the software consists of administrative and nursing process screens. The assessment is automatically selected according to age group, the nursing diagnoses are suggested by the system after information is inserted, and can be indicated by the nurse. The interventions for the chosen diagnosis are selected by structuring the care plan. Conclusion: the development of this tool used to document the nursing actions will contribute to decision-making and quality of care.